2007
DOI: 10.1063/1.2429730
|View full text |Cite
|
Sign up to set email alerts
|

Flatband voltage shift of ruthenium gated stacks and its link with the formation of a thin ruthenium oxide layer at the ruthenium/dielectric interface

Abstract: Fabrication of advanced La-incorporated Hf-silicate gate dielectrics using physical-vapor-deposition-based in situ method and its effective work function modulation of metal/high-k stacks

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…223,224 However, for polycrystalline Ru, no 3D oxide growth has been observed, 265,266 with only increased roughening being detected. 267 In this thesis, we want to have a tool that allows us to recognize such (possible) 3D features growing in our relevant polycrystalline Ru films during thermal oxidation.…”
Section: Motivation For Its Usementioning
confidence: 99%
See 4 more Smart Citations
“…223,224 However, for polycrystalline Ru, no 3D oxide growth has been observed, 265,266 with only increased roughening being detected. 267 In this thesis, we want to have a tool that allows us to recognize such (possible) 3D features growing in our relevant polycrystalline Ru films during thermal oxidation.…”
Section: Motivation For Its Usementioning
confidence: 99%
“…265,266,267 Although, an increased roughening has been detected at enhanced temperatures in these studies, 267 it has not been recognized as 3D growth, and only thin film RuOx growth has been reported. 265,266 In this thesis (Chapter 3), we report on the simultaneous 2D (thin film) and 3D (nano-column) growth of ruthenium oxide, experimentally observed for thermally oxidized polycrystalline Ru thin films. In addition, it is also found that the thin film oxide does not grow as a single layer but a combination of two layers on top of each other, a low density RuOx (2<x≤3) layer on top of a near bulk density RuO2 layer.…”
mentioning
confidence: 98%
See 3 more Smart Citations